1990
DOI: 10.1002/hep.1840120308
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid-induced changes of plasma and urinary bile acids in patients with primary biliary cirrhosis

Abstract: Ursodeoxycholic acid treatment of patients with primary biliary cirrhosis may lead to relief of pruritus and improvement of biochemical liver tests. The changes in serum and urinary bile acids induced by ursodeoxycholic acid treatment were studied. After 29 patients with primary biliary cirrhosis were treated with ursodeoxycholic acid (750 to 1,000 mg/day) for 6 to 12 mo because of an increase in ursodeoxycholic acid, total plasma bile acids increased from 30.5 +/- 6 mumol/L (mean +/- S.E.M.) to 52.7 +/- 11.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 19 publications
6
48
0
1
Order By: Relevance
“…38 Therefore, it can be speculated that cholestasis may initiate alternative metabolic pathways leading to these atypical compounds. It is unlikely that this fraction derives from previous UDCA therapy for three reasons: first, these compounds are different from the metabolites of UDCA reported in other studies 39,40 ; second, this fraction dramatically decreased during the administration of both UDCA and TUDCA; and, finally, a similar amount of unusual bile acids was also found in the three patients who had never received UDCA or TUDCA before the study. This heterogeneous fraction, also containing several highly hydrophobic metabolites, was proportionally reduced to a greater extent by TUDCA administration than with UDCA.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…38 Therefore, it can be speculated that cholestasis may initiate alternative metabolic pathways leading to these atypical compounds. It is unlikely that this fraction derives from previous UDCA therapy for three reasons: first, these compounds are different from the metabolites of UDCA reported in other studies 39,40 ; second, this fraction dramatically decreased during the administration of both UDCA and TUDCA; and, finally, a similar amount of unusual bile acids was also found in the three patients who had never received UDCA or TUDCA before the study. This heterogeneous fraction, also containing several highly hydrophobic metabolites, was proportionally reduced to a greater extent by TUDCA administration than with UDCA.…”
Section: Discussionmentioning
confidence: 57%
“…hydroxy, 6␣-hydroxy and the partial side-chain oxidized unsaturated metabolite, ⌬ 22 -UDCA, and have been previously identified as specific metabolites of UDCA. [39][40][41][42][43] The reduced biotransformation of TUDCA may be explained in terms of the protection of the molecule afforded by the presence of the amino acid in the side-chain. 44 As expected, TUDCA was not completely resistant to biotransformation during enterohepatic recycling, because deconjugation of the bile acid, followed by reconjugation with glycine, presumably accounts for the increase in glycine-conjugated UDCA in duodenal fluid during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even the three individuals who did not have unusual trihydroxy bile acids in urine before UDCA treatment, had detectable levels of these bile acids on the fourth day of UDCA treatment. The induction of unusual trihydroxy bile acids by UDCA treatment was previously reported in patients with primary biliary cirrhosis 16,17 but the improvement of liver function with long-term UDCA therapy is assumed to play a part in the appearance of these bile acids in the reported cases. The present study revealed, for the first time, that UDCA treatment for 3 days is adequate for assessing bile acid-hydroxylation in the liver.…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, we cannot exclude the possibility that inadequate drug absorption or bile enrichment diminished its efficacy. Such studies, however, have been performed in chronic hepatitis 12,29 and PBC, [30][31][32] and these deficiencies have not been encountered, even in individuals receiving lower doses of ursodeoxycholic acid than those administered in our study. Based on these experiences, we had no reason to assume unprecedented deficiencies in absorption as a basis for our discouraging results.…”
Section: Discussionmentioning
confidence: 81%